MultivariateAnalysis: um pacote R para análise multivariada. (Acta Scientiarum. Agronomy, 2025)
Statistical analysis is essential in research. As modern production processes evolve, the increasing volume of data needing processing has demanded techniques like multivariate analysis for simultaneous data handling. Multivariate analyses are typically complex and often require statistical software. The MultivariateAnalysis package, an R package available on the CRAN platform, was developed to facilitate these analyses. Introduced in 2021 by researcher Alcinei Místico Azevedo, it encompasses techniques such as principal component analysis, principal coordinate analysis, hierarchical clustering, Mantel correlation, dendrograms, canonical variables, dissimilarity measurements, and multivariate variance analysis. This paper aims to detail the MultivariateAnalysis package, offering a practical guide from initial steps to results, enhancing user understanding of the package's functions and potential applications. Its open-source code permits function additions. As of 2024, MultivariateAnalysis has reached version 5.0, featuring enhancements in graphical functions that provide a simple, flexible, and intuitive workspace applicable across various knowledge domains